USG Guided Interscalene Nerve Block as Perioperative Management in Close Fracture Clavicula with Traumatic Brain Injury Patient and Contusio Pulmonum: A Case Report - Prasetya, Novandi Lisyam; Muhammad Husni Thamrin; Ellen Josephine Handoko (Journal of Anesthesiology and Clinical Research, 2024)
Introduction: Blunt trauma from motor vehicle accidents (MVA) often results in multisystem injuries, including chest, head, and musculoskeletal injuries. Management of these complex injuries requires a multidisciplinary approach and can present unique anesthetic challenges. Case presentation: A 22-year-old man was treated in the emergency department (ER) after experiencing an MVA. The patient experienced chest and shoulder pain and was found to have anemia, increased creatinine, respiratory acidosis, prolonged prothrombin time (PT), and increased serum glutamic oxaloacetic transaminase (SGOT). Radiological examination revealed left tension hydropneumothorax, right hydropneumothorax, bilateral lung contusions, fractures of the ribs, clavicle, and scapula. In addition, the patient also experienced subarachnoid hemorrhage (SAH) in the left parietotemporal region and right cistern (Fisher Scale III), brain edema, right pneumo-orbita, type III septal deviation, bilateral inferior nasal concha hypertrophy, and concha bullosa on the medial nasal concha. The patient's physical status was assessed as ASA III. The patient underwent open reduction and internal fixation (ORIF) with an S-plate on the right clavicle. Anesthesia was provided with an interscalene block using 0.375% levobupivacaine and premedication with Fentanyl and Midazolam. Conclusion: This case highlights the complexity of managing blunt trauma patients with multisystem injuries. A multidisciplinary approach, including careful airway management, hemodynamic monitoring, and selection of appropriate anesthetic techniques, is essential for optimal results.